Blinatumomab overcomes poor prognostic impact of measurable residual disease in pediatric high-risk first relapse B-cell precursor acute lymphoblastic leukemia - Locatelli, Franco; Eckert, Cornelia; Hrusak, Ondrej; Buldini, Barbara; Sartor, Mary; Zugmaier, Gerhard; Zeng, Yi; Pilankar, Deepali; Morris, Joan; von Stackelberg, Arend (Pediatric blood & cancer, 2022)
BACKGROUND: Blinatumomab, a CD3/CD19 BiTE® (bispecific T cell engager) molecule, was superior to high-risk third course consolidation chemotherapy (HC3) in prolonging event-free survival (EFS) in children with high-risk first relapse B-cell precursor acute lymphoblastic leukemia (B-ALL). Here, we report results from a post hoc measurable residual disease (MRD) analysis of this phase 3 study (NCT02393859). PROCEDURE: Children >28 days and <18 years with high-risk first-relapse B-ALL in cytomorphological complete remission (M1 marrow, <5% blasts) or with M2 marrow (≥5% and <25% blasts) after induction and two cycles of high-risk consolidation chemotherapy (baseline) were enrolled in this trial. Patients received one cycle of blinatumomab (15 μg/m2 /day, 4 weeks, continuous intravenous infusion) or HC3. The primary endpoint was EFS. In this post hoc analysis, patients with MRD <10-4 by PCR were grouped as having positive but not quantifiable (pbnq) or undetectable disease. RESULTS: A higher proportion of patients with MRD <10-4 had undetectable versus pbnq disease after blinatumomab (day 29) than after HC3 (p = 0.0367). Of the 22 patients with MRD ≥10-4 at baseline who achieved MRD remission after blinatumomab, 20 (91%) achieved MRD <10-4 remission by day 15. Patients treated with blinatumomab had improved EFS and overall survival compared with those treated with HC3 independent of end-of-induction or baseline (end-of-second consolidation) MRD levels. CONCLUSIONS: Blinatumomab was more efficacious than HC3 regardless of MRD status before treatment. These data support the role of blinatumomab in inducing deep MRD remission, negating the poor prognostic value of MRD.
Keywords: recidiva; MRD; Neoplasm, Residual; Humans; acute lymphoblastic leukemia; dítě; Burkittův lymfom; Child; Lymphoma, B-Cell; lidé; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; protilátky bispecifické; B-buněčný lymfom; prognóza; blinatumomab; Recurrence; akutní lymfatická leukemie; Acute Disease; pre-B-buněčná leukemie; Precursor Cell Lymphoblastic Leukemia-Lymphoma; prognosis; Antibodies, Bispecific; akutní nemoc; Prognosis; Burkitt Lymphoma; reziduální nádor; pediatric